2020
DOI: 10.3390/v12101200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in the Pathogenesis of Viral Infections in Humans

Abstract: Most cells can release extracellular vesicles (EVs), membrane vesicles containing various proteins, nucleic acids, enzymes, and signaling molecules. The exchange of EVs between cells facilitates intercellular communication, amplification of cellular responses, immune response modulation, and perhaps alterations in viral pathogenicity. EVs serve a dual role in inhibiting or enhancing viral infection and pathogenesis. This review examines the current literature on EVs to explore the complex role of EVs in the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 140 publications
(274 reference statements)
0
52
0
1
Order By: Relevance
“…In both instances, viral infections are the most common cause [ 83 ]. On a cellular level, viruses can exploit the host’s machinery for vesicle biogenesis and use it to their advantage [ 84 ]; sEVs from infected cells carry viral genetic material, proteins, and, in some cases, whole viruses. As one vesicle contains several virus particles, this type of transmission is highly infectious [ 85 ].…”
Section: Role Of Sevs In Inflammatory Airway Diseasesmentioning
confidence: 99%
“…In both instances, viral infections are the most common cause [ 83 ]. On a cellular level, viruses can exploit the host’s machinery for vesicle biogenesis and use it to their advantage [ 84 ]; sEVs from infected cells carry viral genetic material, proteins, and, in some cases, whole viruses. As one vesicle contains several virus particles, this type of transmission is highly infectious [ 85 ].…”
Section: Role Of Sevs In Inflammatory Airway Diseasesmentioning
confidence: 99%
“…研究发现, ZIKV可感染胎盘巨噬细胞和滋养层细胞, 在滋养层细胞内质网采用胎盘外泌体途径通过胎盘滋 养层 [29] . 单核细胞是ZIKV进入大脑的载体 [30] , 大脑中 的多种脑细胞在发育过程中表达高水平的受体TAM家 族(Tyro3/Axl/Merreceptortyrosinekinase)的酪氨酸蛋白 激酶受体(AXL).…”
Section: 主要临床表现unclassified
“…Evidence suggested that exosomes carry materials from one cell to other cells for initiation and exaggeration of disease [ 6 ]. Exosomes are also involved in viral spread, immune regulation, and antiviral response during infection [ 7 , 8 , 9 ]. Little is known about exosomes of SARS-CoV-2-infected patients and their role in pathogenesis.…”
Section: Introductionmentioning
confidence: 99%